Social Intelligence Of Students In The Al-Halimy Sesela Islamic Boarding School - Ermawati (Pesantren Reviews, 2023)
This study aims to determine the social intelligence of female students at the Al-Halimy Sesela Islamic boarding school. The research was carried out at Al-Halimy Islamic Boarding School, especially Anwarul Halimy Sesela's daughter's boarding school. This study used a qualitative approach with a descriptive research type. In this research, data collection used a purposive sampling method with data collection using interview, observation, and documentation methods which were then analyzed using data triangulation. The results showed that the students were able to understand what other people were thinking and feeling, as well as what the person concerned (observer, perceiver) was thinking and feeling about the conditions that were being experienced by other people, without the person concerned losing control of himself then from that understanding the students made an effort help his friend. This is inseparable from the strength of the situation to what extent the similarities between the observer and the target. The higher the level of equality, the greater the opportunity for the observer to empathize, in this case, the equality of residence, ethnicity, religion, nation, etc. Suggestions for further researchers related to social intelligence, namely the need for further research related to factors that influence the social intelligence of students, so that later there is sufficient research to explain in more detail about the social intelligence of students, especially at the Al-Halimy Sesela Islamic boarding school.